(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This current article makes an attempt to provide a comparative analysis of the codification of legislation in various legal systems. The authors analyze the features of the systematization of legislation in the countries of the Romano-Germanic and Anglo-Saxon legal systems. Several general scientific methods and the methods of logical cognition are utilized in the study, including analysis and synthesis, systemic, functional and formal-logical approaches. Based on the results of the study, it can be concluded that it is the continental legal tradition that is most conducive to codification activity. The low volume of statutory legal norms in the Anglo-Saxon legal system impedes codification, but provides adequate regulatory flexibility. At the same time, recently in common law countries there has been a tendency to increase the share of statutory law in the regulation of public relations. In this regard, the importance of codification work increases in the systematization of legislation.